2020
DOI: 10.1111/1346-8138.15250
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17A suppresses granular layer formation in a 3‐D human epidermis model through regulation of terminal differentiation genes

Abstract: Immunotherapies targeting interleukin (IL)‐17 greatly improve plaque psoriasis. Most previous studies on IL‐17 focused on the T‐helper (Th)17 immune response, but investigation of the effects of IL‐17A on psoriatic epidermal structure are limited. Using an in vitro 3‐D human epidermis model, we investigated the effects of IL‐17A and IL‐17C on morphological changes and gene expression. IL‐17A directly suppressed the formation of the granular layer, whereas IL‐17C did not. IL‐17A significantly downregulated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…The observed improvement in the patients’ skin lesions supports the clinical importance of our findings. RNA-Seq data sets from a patient before and after treatment revealed that in addition to suppressing the inflammatory response, ustekinumab restored expression of structural/adhesive proteins important for maintaining epidermal architecture, consistent with previous reports that IL-17A can downregulate differentiation and cornified envelope-related genes ( 49 ). These adhesive proteins included the genetic target, Dsg1, which was restored at cell-cell borders in treated patient epidermis.…”
Section: Discussionsupporting
confidence: 88%
“…The observed improvement in the patients’ skin lesions supports the clinical importance of our findings. RNA-Seq data sets from a patient before and after treatment revealed that in addition to suppressing the inflammatory response, ustekinumab restored expression of structural/adhesive proteins important for maintaining epidermal architecture, consistent with previous reports that IL-17A can downregulate differentiation and cornified envelope-related genes ( 49 ). These adhesive proteins included the genetic target, Dsg1, which was restored at cell-cell borders in treated patient epidermis.…”
Section: Discussionsupporting
confidence: 88%
“…Some of the strongest candidates seen in the paired mother–child transcriptomic analyses were MX1 , IFI6 , and IFIT3 , all members of the interferon signaling pathway, identified here as the most differentially expressed canonical pathway specific to maternal atopy. The shared DEGs have previously been connected to AD, 70,84,85 asthma, 86–88 and inflammatory processes 89–91 . For all nine DEGs found in mother and child pairs, eQTM relationships depending on maternal atopy were shown.…”
Section: Discussionmentioning
confidence: 84%
“…The shared DEGs have previously been connected to AD, 70,84,85 asthma, [86][87][88] and inflammatory processes. [89][90][91] For all nine DEGs found in mother and child pairs, eQTM relationships depending on maternal Determining risk factors at an epigenetic and transcriptomic level exposes many limitations given the complexity of the diseases, heterogeneity within cohorts, and sizes of the cohorts. The overall study population on a genome-wide level may be considered small.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation that is induced by IL-17A contributes greatly to the defense against bacterial, fungal, and viral infections, but excessive inflammation can lead to autoimmune diseases and the creation of unfortunate conditions in the skin, such as psoriasis and hidradenitis suppurativa (HS), as described below. Additionally, IL-17A is directly involved in epidermal differentiation, as described below, and this may also be related to the formation of a pathological epidermis, such as psoriasis [22][23][24].…”
Section: Il-17amentioning
confidence: 99%